2017
DOI: 10.1080/13813455.2017.1369547
|View full text |Cite
|
Sign up to set email alerts
|

Glucose metabolism and metabolic flexibility in cultured skeletal muscle cells is related to exercise status in young male subjects

Abstract: We hypothesised that skeletal muscles of healthy young people have a large variation in oxidative capacity and fibre-type composition, and aimed therefore to investigate glucose metabolism in biopsies and myotubes isolated from musculus vastus lateralis from healthy males with varying degrees of maximal oxygen uptake. Trained and intermediary trained subjects showed higher carbohydrate oxidation in vivo. Fibre-type distribution in biopsies and myotubes did not differ between groups. There was no correlation be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 45 publications
4
18
0
Order By: Relevance
“…Selected donor characteristics are presented in Table 1 , and have been presented in full previously 18 . As expected the athletic subjects performed at a higher workload max and they also had higher maximal fat oxidation in vivo , as determined during an incremental test, compared to sedentary subjects (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Selected donor characteristics are presented in Table 1 , and have been presented in full previously 18 . As expected the athletic subjects performed at a higher workload max and they also had higher maximal fat oxidation in vivo , as determined during an incremental test, compared to sedentary subjects (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…BMI, body mass index; VO 2max , maximal oxygen uptake; WHR, waist-to-hip ratio. Complete set of donor characteristics have been reported in full previously 18 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…With longer task durations (>3 h) an increased reliance on exogenous CHO oxidation later in exercise could enhance liver glycogen sparing and could improve subsequent performance outcomes. Furthermore, with improved training status comes improved capacity to oxidize substrates [ 20 , 21 ] which might drive the CHO provision threshold beyond 40–60 g·h −1 .…”
Section: Discussionmentioning
confidence: 99%
“…Donors were 25.5 (±0.95) (mean ± SEM) years old with a body mass index of 22.1 (±0.8) kg/m 2 . More details about the donor cohort used in this study, as well as characteristics of myotubes can be found in the study by Lund et al 28 . Muscle biopsies were obtained after informed written consent and approval by the National Committee for Research Ethics, Oslo, Norway (2011/2207 REK South East B).…”
Section: Methodsmentioning
confidence: 99%